High school students' perceptions of the modern teacher image - E. A. Petrova; N. N. Akimova; A. V. Romanova; I. E. Sokolovskaya (Russian State Vocational Pedagogical University, 2020)
Introduction. In modern Russian society, the requirements for the general level of the school educational process have resulted not only from the demands related to the content of educational programmes, but also from sufficiently high requirements for a teacher personality. A modern teacher has to build up a holistic and harmonious image, ranging from stylish and modern appearance to a high level of professionalism. The image of a teacher directly or indirectly influences the effectiveness of the mutual action of the members of education. Therefore, the reflection of various aspects, which form the image of the teacher in order to correct it in accordance with the existing school realities, is a relevant direction of psychological research.The aim of the present research is to identify the most significant and preferred characteristics of the image of a modern teacher in the perceptions of high school students.Methodology and research methods. The methodological framework of the research is based on psychosemiotic approaches in social psychology: the concept of modern psychosemiotics of communication by E. A. Petrova and theoretical positions of objective and subjective psychosemantics by E. Yu. Artemyeva, V. F. Petrenko and A. G. Shmelev. The selection of psychodiagnostic methods was based on three-factor models of imageological space organisation. The perceptions of high school students about such characteristics of the image as the appearance of the "ideal" and "bad" teacher were studied using a projective technique. The method of free semantic survey, supplemented by the method of "Factor Space of the Teacher Image" by E. A. Petrova, was used to study personal, professional and communicative features. Such method allowed the authors to structure the students' ideas about the image of the teacher by categories related to personal characteristics: attitude to own profession, attitude to students and educational activities. The images of teachers of different types were created through the psychosemantic technique developed by D. Peabody in A. G. Shmelev's adaptation. The non-parametric criterion of differences - Mann-Whitney U-test was employed to identify the differences in high school students' ideas about the image of the modern "ideal" teacher depending on gender.Results and scientific novelty. It was established that the attitude of high school students to the teacher mostly depends on teacher's professional and personal qualities. School students especially highlighted the following aspects: the high level of mastery over the subject taught; teachers' ability to interest students in educational material; cooperation with students and objective assessment of their knowledge. Significant positive personality characteristics included the ability to interact constructively and kindly with each student, as well as the high level of activity and positive energy of the teacher. The students think that a teacher's appearance does not play a determining role. However, the respondents noted that it is important for them that the teacher prefers the business style of clothing and looks modern and neat.Practical significance. The research results can be applied in the practice of school psychological service and in coaching activities in order to inform the teaching staff and interested teachers about the role of image when building effective interactions in the system "teacher-student".